2022
DOI: 10.7759/cureus.30225
|View full text |Cite
|
Sign up to set email alerts
|

Role of High-Sensitivity C-reactive Protein (Hs-CRP) in Non-communicable Diseases: A Review

Abstract: Non-communicable diseases like cardiovascular diseases, cerebrovascular diseases, diabetes mellitus, and cancer are very common causes of death worldwide. Therefore, the need to search for novel, affordable, and easily accessible biomarkers and risk factors for non-communicable diseases continues, which can predict the future risk of having these diseases with greater accuracy and precision. In this context, among available biomarkers, high-sensitivity C-reactive protein (Hs-CRP) is considered to be the best-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 84 publications
1
27
0
Order By: Relevance
“…Previous studies have shown that CRP can promote atherosclerosis, blood stagnation, and plaque formation. TH can lead to blood hyperviscosity syndrome, so the increase in CRP may be related to this reason ( 32 , 33 ). According to the brain MR results and the elevated CRP in both groups in our research, we believe that the heavier the HIE, the higher the risk of hs-CRP elevation after mild hypothermia treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CRP can promote atherosclerosis, blood stagnation, and plaque formation. TH can lead to blood hyperviscosity syndrome, so the increase in CRP may be related to this reason ( 32 , 33 ). According to the brain MR results and the elevated CRP in both groups in our research, we believe that the heavier the HIE, the higher the risk of hs-CRP elevation after mild hypothermia treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Restriction of sleep reduces insulin sensitivity the next day by increasing cortisol levels in the nighttime ( 45 , 46 ). In contrast, some infection markers such as IL-6, and C-reactive protein increase in people who report prolonged sleep, which accelerates the progression of diabetes and its complications ( 47 , 48 ). Therefore, based on the results we obtained; it can be considered sleep duration/quality as a risk marker in monitoring diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The median of hsCRP of 1.26 µg mL −1 in women and 1.05 µg mL −1 in men fall in the range of 1–2 µg mL −1 which were associated with a higher risk for cardiovascular disease. [ 33 ] All data were shown as mean and standard deviation (SD) or standard error of mean (SEM) in tables and graphs. Statistical significance was assumed at p < 0.05.…”
Section: Methodsmentioning
confidence: 99%